# trig

posted by .

Prove : (sinA-cosA+1)/(sinA+cosA-1) = (1+sinA)/cosA

• trig -

multiply top and bottom of the left side by
(sinA + cosA + 1) and expand carefully

remember sin^2A + cos^2A = 1
and in the bottom replace the
-cos^2A with (1-sin^2A)

## Similar Questions

1. ### Maths

Hi, can someone give me the answer to this question: secA-tanA=1/4. Find cosA I got: CosA=4(1-sinA) Is my answer good?
2. ### maths(trigonometry)

prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA
3. ### trig

Please help me how to do this: 1) 1 + sina*cosa / (cosa + sina)^2 = 2) sina + cosa / 1- 2sin^2a =
4. ### trig

I need to count this: a) 1-tg^2a/1+ctg^2a, when sina =2/3 b) 1-tg^2a/1-ctg^2a, when cosa= -1/3 c) tga * cos^2a, when sina + cosa=5/7 d) tg^2a + 1/sina * 1/cosa + ctg^2a, when tga + ctga =5
5. ### trig

prove that :cosA-sinA+1/cosA+sinA-1=cosecA+cotA
6. ### further mathematics

Let P=(cosA sinA) (sinA cosA) Q=(cosB sinA) (sinB cosA) show that PQ=(cosA(A-B) sin(A B)) (sinA(A B) cos(A-B))
7. ### trig

Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA
8. ### trigonometry

Prove : 1 + Sin2A/ Cos2A = CosA + SinA / CosA- SinA
9. ### trigonometry

x×sin^3A=y , cos^3A = sinA × cosA , x×sinA= y×cosA , then prove that x^2+ y^2= 1 I have no idea
10. ### Maths

Prove that [sinA/(1-cosA)-(1-cosA)/sinA]*[cosA/(1+sinA)+(1+sinA)/cosA]=4cosecA I the second part as 2 secA

More Similar Questions